PENINGKATAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA MELALUI MODEL PEMBELAJARAN RESOURCE BASED LEARNING (RBL) DI KELAS VIII SMP NEGERI 4 NIRUNMAS KABUPATEN MALUKU TENGGARA BARAT - Alexander Batmomolin; M Nur Matdoan (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: In general, Biology learning in Nirunmas Maluku, West Nusa Tenggara 4 Middle School, is still teacher-centered, namely using the lecture method, so that the learning outcomes obtained by students are not maximal or inadequate for School KKM. Method: The type of research used is descriptive, using the Resource Based Learning learning model to master the concept of the human digestive system in class VIII Nirunmas 4 Middle School. This research was conducted on February 25 - March 25, 2018. Results: Achievement of learning outcomes before using the Resource Based Learning (RBL) learning model with an average student achievement in the initial test was 62%, while after using the Resource Based Learning (RBL) learning model the average student achievement in the final test was 81, 32% and the final score was 84.33%. Conclusion: There is an increase in students' understanding in the learning process using the Resource Based Learning (RBL) learning model